Primary abdominal cocoon syndrome manifesting with Chilaiditi syndrome and intestinal obstruction: A case report - Ali Tajaddini; Mohammadmehdi Fallahi; Hoda Haghshenas; Soheila‐sadat Nourmohammadi; Leila Ghahramani; Reza Shahriarirad (Clinical Case Reports, 2024)
Key Clinical Message Abdominal cocoon syndrome and Chilaiditi syndrome are rare etiologies of bowel obstruction which have to be considered in patients with obstructive symptoms. Patients can profit from surgical management rather than non‐surgical approach. Abstract Encapsulating peritoneal sclerosis or abdominal cocoon syndrome (ACS) is an uncommon cause of intestinal obstructions associated with encapsulation of the small bowel by a fibro collagenous sac. Clinical presentations of ACS are unspecific and most patients are diagnosed intraoperatively. Moreover, Chilaiditi syndrome is another rare cause of bowel obstruction defined by interposition of colon and liver. There is no reported relation between these two conditions and surgical intervention is the suggested approach for severe bowel obstruction following them individually. We present a case with both conditions and describe our approach. A 47‐year‐old male presented with complaints of colic abdominal pain and distention, nausea and several attacks of bilious and nonbilious vomiting, anorexia, and constipation in the last 10 days before his admission. Laboratory data were normal and abdominal X‐ray showed large dilation at the distal part of the bowel without air fluid level. The patient underwent explorative laparotomy and a mass‐like lesion containing necrotic bowel and a whitish spleen accompanied by a complete anterior‐rotated liver was found. The encapsulated bowel and the spleen were resected followed by the complete resolution of symptoms in the patient. The intestinal obstruction caused by ACS is mostly approached by surgery to prevent the fatal sequela of this condition.